Potential of Fruits to Improve Dyslipidemias: A Pilot Review - Flores Flores MA; Flores Flores LA; Romero Yupanqui SD (Vascular Health and Risk Management)
Miguel Angel Flores Flores,1,* Luis Antonio Flores Flores,2,* Serafín Dernali Romero Yupanqui3,* 1Faculty of Food Industry, Universidad Nacional de la Amazonía Peruana, Iquitos, Maynas, Loreto, 16002, Perú; 2Faculty of Chemical Engineering, Universidad Nacional de la Amazonía Peruana, Iquitos, Maynas, Loreto, 16002, Perú; 3Faculty of Medicine, Universidad Nacional de la Amazonía Peruana, Iquitos, Maynas, Loreto, 16002, Perú*These authors contributed equally to this workCorrespondence: Miguel Angel Flores Flores, Faculty of Food Industry, Universidad Nacional de la Amazonia Peruana, Iquitos, Maynas, Loreto, 16002, Perú, Tel +51987282346, Email mianfloflo@gmail.comAbstract: Dyslipidemia is a condition characterized by excessive lipids in the blood plasma, including triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and decreased levels of high-density lipoprotein cholesterol (HDL-C), which is generated mostly due to obesity. This study aims to summarize research conducted on rats and humans regarding the potential of eight fruits in reducing dyslipidemia and their associated health benefits (eg, reduction of free radicals, hypoglycemic effects, weight reduction, lowering of blood pressure, and anti-inflammatory properties). The studied fruits include pomegranate, star fruit, Rosa roxburghii, pineapple, tree tomato, coffee, apple, and passion fruit. Various parts of these fruits, such as the root, leaves, stem, peel, and pulp, were analyzed for their effects. These fruits are edible, widely available, and cost-effective when purchased during the harvest season (Graphical abstract). Keywords: fruits, dyslipidemias, humans, rats, benefits